The regulation of chromatin and transmission of epigenetic information by the heterochromatin protein 1, binding protein 3 (HP1BP3) in normal and colorectal cancer cells - Kattan, Shahad (2017)
The heterochromatin-associated proteins are subject to several different posttranslational modifications; hence, their level must be tightly controlled; otherwise as transcription factor co-repressor(s) complexes with these proteins, it may lead to stable silencing. An obvious mechanism to limit the expression time of a protein is to destroy it via the ubiquitin-proteasome system. FBXW7 (F-box and WD repeat domain–containing 7) is an E3-ligase targets transcriptional modulators and proto-oncogenes for degradation with crucial functions in cell-fate determination and tumorigenesis. In addition, most of current studies focused on epigenetic modifications that influence on the core histones within the euchromatin-heterochromatin transition, whereas the heterochromatin proteins and their partners’ identity remained largely unclear.